La comida ritual en las fiestas de las veintenas mexicas : un acercamiento a su tipología y simbolismo - Elena Mazzetto (Les Cahiers ALHIM)
This article provides insight into the different types of ritual food prepared and consumed in the ritual context of the celebrations of the veintenas of the Mexican solar year. First of all, the analysis is to know the contexts of the word tlacatlacualli, employed to call the meals prepared during periods of ritual fasting. Then, to consider the symbolic language of the offerings from two significant characteristics : size, which could vary based on the ceremony, and form. In particular, to establish outstanding relationships between the appearance of the food and the fields of action of the supernatural recipients to see some examples. Finally, to tackle the analysis of relationships between a specific food prepared during the festivity of the veintenas and the food prepared for the deceased, presenting an interpretive hypothesis that could explain these similarities.